CORPORATE GOVERNANCE DAN KINERJA KEUANGAN PADA PERBANKAN DI UNI EMIRAT ARAB - Fatkhur Rohman (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2015)
Based on the background of the earlier studies accompanied by so many research problem and research gap where the result of previous studies indicate that there is an inconsistency, then the effects of corporate governance mechanism on the corporate financial performance still needs to be further researched.The current study uses a data sample of bank financial statements included in the United Arab Emirates bank stocks period 2009-2012. By using purposive sampling of data obtained as much as 88 financial statements of companies that are eligible to be used as samples in this study. The data in this study was obtained from the banks financial performance summary report from the website of the bank stocks United Arab Emirates (www.adx.ae and www.dfm.ae). The technique used to analyze the data is multiple regression techniques.The results of this study is that variables examined in the study are, board size, background of director’s education, number of board meeting, and proportion of independent board of bank ( simultaneously ) have an influence on the Bank's Financial Performance (Ratio ofOperating Expenses toOperating Income) Bank.